Identifikasi Penyakit Bakterial Pada Benih Sidat (Anguilla marmorata) di Balai Budidaya Air Tawar Tatelu - Kusen, Kevin Octavian; Tumbol, Reiny A; Manoppo, Henky (e-Journal BUDIDAYA PERAIRAN, 2015)
This study aimed to identify the bacterial disease in cultured eel elvers (Anguilla marmorata). The samples used for this study were taken from the Tatelu Freshwater Aquaculture Center. The samples taken were elvers (juvenile life stage of A. marmorata) which showed clinical symptoms of bacterial infection such as bleeding in the chest, abdomen, and the base of the fin, passive movement, weakness, and loss of balance of the body, loss of appetite, some wounds on back fin, chest, and tail, and the body was not slippery/shiny. Three elvers with the size of 4-6 cm, and weigh about 0.2 g were taken as samples. The organ chosen to be targeted for isolation was head kidney. Each sample was isolated twice as replicates and streaked on Triptic Soy Agar (TSA) medium. First replicates were identified in the Tatelu Health Lab of Freshwater Aquaculture, and the second replicates were identified in North Sulawesi Provincial Health Lab. Bacterial identification was done through a series of observations and morphology of bacterial colonies through gram stain, followed by biochemical tests through oxidase test, catalase test, Triple Sugar Iron Agar (TSIA) test, H2S production test, motility test, O/F test, and Simmons Citrate Agar (SCA) test. Water quality parameters that were measured included temperature, disolve oxygen, pH, and ammonia. Based on identification of bacteria in cultured elvers in Tatelu Freshwater Aquaculture Center, the elver samples had been infected with bacterial Aeromonas hydrophila. Keywords: elver, identification, Aeromonas hydrophila, Tatelu Freshwater Aquaculture Center